The Impact of Tour Guide Service Quality and Tourist Experience Towards Tourist Satisfaction in Discova Indonesia Tour and Travel - I Nyoman Wahyu Adi Permana; Putu Ayu Aryasih; Ida Bagus Putu Puja (J-TRUE: Journal of Travel and Leisure, 2024)
Customer satisfaction can be defined as outcome-based satisfaction that describes satisfaction as the end state of the consumption experience, or as a process that emphasizes the perception, evaluation, and psychological processes that contribute to customer satisfaction. One of the factors that can affect customer satisfaction is the quality of tour guide services and also the tourist experience. The purpose of this study is to find out how the quality of tour guide services and the tourist experience affects tourist satisfaction. This research was conducted at the Discova Indonesia Travel Bureau by taking a sample of 100 respondents who were tourists. The data collection method uses a questionnaire and the collected data is analyzed using multiple regression analysis. The results of data analysis show that the quality of tour guide services has a positive and significant effect on tourist satisfaction. These results can be concluded that the higher the quality of tour guide services provided by the Discova Indonesia Travel Bureau, the more satisfaction tourists will feel. Tourist experience has a positive and significant effect on tourist satisfaction. These results can be concluded that the better the tourist experience obtained from the Discova Indonesia Tourism Travel Bureau, the more tourist satisfaction will increase.